The Effect of Ms. Teams on Math Learning Motivation and Its Implications for HOTS Skills - Hanif Jauhar Noor; Arief Agoestanto (USN Kolaka, 2023)
The ability to think in a higher order is one of the essential abilities because every concept in mathematics is interconnected. This study aims to analyze the improvement of students' higher-order thinking skills and motivation to learn mathematics. The type of research is a combination (mixed methods) with a sequential explanatory design. The sampling technique uses cluster random sampling technique. The sample of this study was class XI IPS 4 (experiment) and XI IPS 3 (control) SMAN 3 Cirebon Instrument. This study used tests, questionnaires of motivation to learn mathematics, observation sheets of learning implementation, and data analysis techniques. The results of this study were (1) the acquisition of tests using the experimental and control class N-Gain test was 0.67 and 0.43, (2) student learning motivation in the experimental and control classes was in a suitable category, (3) the results of the student mathematics learning motivation questionnaire obtained anaverage initial percentage of 67.470% to 76.405% and, (4) for the percentage of observation results of the average learning implementation of 89%. This study concludes that student learning motivation in the Microsoft Teamsassisted blendedlearning model can positively improve students' higher-order thinking skills.